Progressive collapse resistance of multistory RC frame strengthened with HPFL-BSP. (November 2021) - Huang, Hua; Huang, Min; Zhang, Wei; Guo, Mengxue; Chen, Zhen; Li, Ming
Abstract: The field of progressive collapse has attracted considerable attention worldwide, while little existing building structure has been constructed with progressive collapse design. Therefore, some researchers began to explore effective strengthening methods to improve the progressive collapse resistance of existing building structures while saving cost, resources, and time. In this paper, two 1-bay-by-2-bay two-story reinforced concrete (RC) frames with the loss of one edge column were constructed and tested, including the control and strengthened specimens. The strengthened specimen was strengthened with high-performance ferrocement laminate and bonded steel plates to investigate the strengthening effectiveness. Based on the data collected during the experiment and simulated results, crack development patterns, load-displacement relations, lateral deformation, load distribution, and the effect of strengthening were discussed. Additionally, the finite-element (FE) simulation and the theoretical analysis for such structure were implemented. The results show that the initial stiffness and bearing capacity of frame increased after strengthening. Increasing the steel strand quantity, the peak load can be significantly increased. The stiffness in different floor will have an effect on the load bearing distribution. Higher stiffness in floor will bear much vertical load. The axial compression on adjacent columns increased while decreased in the diagonal columns. The contribution to bearing capacity of slab is weaker than beams. The slab could share about 2/3 vertical load of beams for control specimens and less than 1/2 vertical load of beams for strengthening specimens.